2021
DOI: 10.1111/trf.16368
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and management of immune thrombocytopenia secondary to COVID‐19: Cleveland clinic experience

Abstract: Background: Immune thrombocytopenia (ITP) is an acquired disease characterized by thrombocytopenia secondary to autoantibodies against platelets. Here, we report the clinical characteristics of coronavirus disease 2019 (COVID-19)-induced ITP cases.Study Design and Methods: We retrospectively reviewed 3255 COVID-19 patients. COVID-19-induced ITP was diagnosed after excluding possible common causes. Bleeding severity was assessed based on the modified World Health Organization (WHO) bleeding severity score. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 9 publications
5
42
0
3
Order By: Relevance
“…Venous thromboembolic events are common in patients with COVID-19. Approximately 10% of patients with COVID-19 in hospitals (non-intensive care unit (ICU)) are diagnosed with venous thromboembolism and 28% of those in ICU 11,32,33,34 . The vaccine-induced adverse events after administration of the adenovirus-based SARS-CoV-2 vaccines (including the ChAdOx1 vaccine) have been described as vaccine-induced immune thrombotic thrombocytopenia (VITT) syndrome or thrombosis with thrombocytopenia syndrome resulting in a venous or arterial thrombosis, including CVST and thrombocytopenia 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Venous thromboembolic events are common in patients with COVID-19. Approximately 10% of patients with COVID-19 in hospitals (non-intensive care unit (ICU)) are diagnosed with venous thromboembolism and 28% of those in ICU 11,32,33,34 . The vaccine-induced adverse events after administration of the adenovirus-based SARS-CoV-2 vaccines (including the ChAdOx1 vaccine) have been described as vaccine-induced immune thrombotic thrombocytopenia (VITT) syndrome or thrombosis with thrombocytopenia syndrome resulting in a venous or arterial thrombosis, including CVST and thrombocytopenia 35 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review involving 45 cases of new-onset ITP in COVID-19 patients reported that 22% of cases were treated with glucocorticoid alone, 29% were treated with IVIG alone, and 24.5% of cases were treated with a combination of glucocorticoid and IVIG [ 7 ]. A recent case series of 11 patients showed that three patients were managed with glucocorticoid alone, one patient was managed with IVIG alone, five patients were managed with a combination of glucocorticoid and IVIG, and two patients were managed with glucocorticoid and eltrombopag [ 8 ]. In summary, literature supports the use of combination IVIG and glucocorticoid as an early treatment modality in patients with active bleeding and severe thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Immune thrombocytopenic purpura (ITP) has been described in numerous case reports and case series in association with SARS-CoV-2. The incidence of ITP in SARS-CoV-2 has been described in one study as 0.34% [64].…”
Section: Sars-cov-2 and Itpmentioning
confidence: 99%
“…The majority of new cases of ITP in SARS-CoV-2 patients have been reported in patients 50-70 years old [10,19,[64][65][66][67][68], although cases in children as young as 1 year and up to age 95 have been reported [64,69]. There have been two reported cases of pregnant women who developed de novo ITP associated with SARS-CoV-2 [64,70]. The increase in prevalence in older age is similar to ITP not associated with SARS-CoV-2 [71,72].…”
Section: Sars-cov-2 and Itpmentioning
confidence: 99%
See 1 more Smart Citation